Аналіз існуючих математичних моделей процесу пресування - Лещенко, І. А.; Шокарев, Олександр Миколайович; В’юник, Ольга Володимирівна; Leshchenko, I.; Shokarev, Oleksandr; Viunyk, Olha (Запоріжжя : ТДАТУ, 2023)
UA: Метод пресування є якісним способом виробництва рослинної олії оскільки зберігаються вихідні корисні якості олії, що зумовлено відсутністю впливу хімічних компонентів. Стаття є частиною циклу робіт, присвячених розробці і впровадженню пресового обладнання для віджиму олії з насіння салору. Метою статті є аналіз математичних моделей процесу пресування для створення в подальшому математичної моделі роботи пресу для віджиму рослинної олії з мезги сафлору. В статті представлено результати аналізу існуючих математичних моделей процесу пресування. Надано загальні рівняння процесу віджиму у виробництві рослинних олій. Наведено математичну модель з розрахунку шнекового преса. Описано загальні підходи визначення поля тиску при розрахунку стисливих течій. EN: The pressing method is a high-quality method of vegetable oil production because the original useful qualities of the oil are preserved, which is due to the absence of the influence of chemical components. The article is part of a cycle of works devoted to the development and implementation of a press device for squeezing oil from salor seeds. The purpose of the article is the analysis of mathematical models of the pressing process for the subsequent creation of a mathematical model of the operation of the press for squeezing vegetable oil from safflower pulp. The article presents the results of the analysis of existing mathematical models of the pressing process. The general equations of the pressing process in the production of vegetable oils are given. A mathematical model for the calculation of the screw press is given, taking into account the pressure zone and the pressing chamber, as well as the law of pressure distribution in the conical zone of the pressing chamber. The system of Navier-Stokes equations for the isothermal flow of a compressible fluid in a cylindrical coordinate system (equation of continuity, equation of motion) and components of the stress tensor are given. General approaches for determining the pressure field in the calculation of compressible flows are described. The application of velocity and pressure variables to the problem of fluid motion calculation is described, as well as the application of the vortex and current function variables to these problems. Boundary conditions are set for the stream function and for the vorticity of the flow. The paper describes the procedure for solving the system of equations for a two-dimensional flow.
Analysis of existing mathematical models pressing process
Лещенко І. А., Шокарев О. М., В’юник О. В. Аналіз існуючих математичних моделей процесу пресування. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 2. C. 151-161.
Keywords: математична модель; аналіз; віджим суміші; шнековий прес; рух рідини; ламінарна течія; завихреність; mathematical model; analysis; mixture pressing; screw press; fluid movement; laminar flow; vorticity